AB1187 What imaging detected pathologies are associated with shoulder symptoms and their persistence? a systematic literature review. (12th June 2018) - Tran, G.; Cowling, P.; Smith, T.; Lucas, A.; Hensor, E.; Barr, A.; Kingsbury, S.; Conaghan, P.
Abstract : Background: Shoulder pain is a very common musculoskeletal complaint and a significant contributor to disability and morbidity. Recovery can be slow and over 50% continue to have pain at 18 months. Shoulder pain has a significant negative impact on quality of life and poses a significant economic burden, with costs estimated to be €345 million per year in the UK alone. Modern imaging modalities can accurately detect soft-tissue pathologies and are increasingly used, but the relationship of imaging findings to patient symptoms remain unclear. Objectives: Our aim was to systematically review the literature to determine what imaging features are associated with symptoms and their progression. Methods: A systematic review using Medline, EMBASE, Cochrane and grey literature was conducted to April 2017. The cross-sectional and longitudinal relationships between imaging-detected abnormalities and symptoms were analysed and associations qualitatively characterised by a best evidence synthesis based on study design, covariate adjustment and the Grade of Recommendations Assessment, Development and Evaluation (GRADE). Modalities included ultrasound, magnetic resonance imaging (MRI), radiographs, positron emission tomography (PET), bone scintigraphy and computerised tomography (CT). Results: 6569 abstracts were screened and 56 papers were included. 50 studies did not adjust for covariates. The majority of studies showed conflicting findings. There was no significant association between most imaging features (rotator cuff tears, tendinopathies, subacromial bursal pathologies, osteoarthritis, calcification, acromial pathologies and adhesive capsulitis) and symptoms amongst high quality, cross-sectional studies. There was low-quality evidence suggesting that enhancement of the joint capsule on MRI and increased uptake of the rotator cuff interval, anterior joint capsule or axillary recess on PET was associated with symptoms in adhesive capsulitis. Based on high-quality, unadjusted longitudinal studies, enlarging rotator cuff tears was associated with an increased incidence of pain. 20 out of 56 studies evaluated more than one pathology, but only one study examined the association of symptoms with a combination of pathologies. Conclusions: There were conflicting results on the association of imaging features with shoulder symptoms and its persistence and the existing evidence was very low in quality. There may be some imaging features associated with adhesive capsulitis symptoms and increasing RC tear may be associated with incident shoulder symptoms. Further high quality studies are required to understand the relationship between imaging and symptoms. Disclosure of Interest: None declared